Public opinion regarding alternative medicine - M. Hammond (AOSIS, 1982)
Fairly widespread disillusionment in medicine since the 1950s (when many wonder drugs proved themselves either ineffective or harmful - or both, and when disease was found to be as prevalent as ever, even if in degenerative and stress-related guises), seems to have coincided with considerable public interest in alternative forms of healing. Some authors have given sympathetic attention to alternatives like homeopathy, chiropractic, herbalism and so on, but most of the literature still deals with these healers in a patronising if not blatantly biased manner. The abundance of emotive, highly critical reporting in the popular press, coupled with the relative lack of detailed, up-to-date studies and the persistence of ideas put forward by those in positions of power and status has caused a situation where most common knowledge about alternatives is nothing short of mythical.